2009
DOI: 10.4081/965
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ATP7B in normal human liver

Abstract: ATP7B is a copper transporting P-type ATPase, also known as Wilson disease protein, which plays a key role in copper distribution inside cells. Recent experimental data in cell culture have shown that ATP7B putatively serves a dual function in hepatocytes: when localized to the Golgi apparatus, it has a biosynthetic role, delivering copper atoms to apoceruloplasmin; when the hepatocytes are under copper stress, ATP7B translocates to the biliary pole to transport excess copper out of the cell and into the bile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…As the cellular The final destination of ATP7B during copperinduced trafficking process has been a matter of debate. In the human liver, immunoreactivity for hepatic ATP7B was observed close to the plasma membrane [56]. However, the results from several laboratories [51,52] agree that ATP7B does not traffic preferentially to the plasma membrane to directly export copper into the bile, as most of the localization of ATP7B in high copper is intracellular (vesicular).…”
Section: Molecular Architecture and Enzymatic Properties Of Atp7b (Wimentioning
confidence: 95%
“…As the cellular The final destination of ATP7B during copperinduced trafficking process has been a matter of debate. In the human liver, immunoreactivity for hepatic ATP7B was observed close to the plasma membrane [56]. However, the results from several laboratories [51,52] agree that ATP7B does not traffic preferentially to the plasma membrane to directly export copper into the bile, as most of the localization of ATP7B in high copper is intracellular (vesicular).…”
Section: Molecular Architecture and Enzymatic Properties Of Atp7b (Wimentioning
confidence: 95%
“…3 Moreover, detailed analysis of human liver biopsies using a polyclonal antiserum specific for ATP7B revealed that ATP7B is localized to the plasma membrane of both hepatocytes and biliary epithelium. 4 To confirm that the copper flush-out from hepatic tissue is not uneven, we extended the previous study and performed laser-ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) on hepatic tissue sections of male homozygous Atp7b null mice. 5 To do so, six-week-old Atp7b À/À mice (n = 6) received an injection of an AAV8 expressing a codon optimized (co) version of an ATP7B mini gene (miATP7B) under the control of the AAT promoter (AAV-AAT-co-miATP7B) at a dose of 1 Â 10 11 vg/mouse, whilst another group of Atp7b À/À mice (n = 5) of the same age were left untreated.…”
mentioning
confidence: 87%
“…ATP7B is expressed most abundantly in hepatocytes, where it transfers Cu + into the lumen of the trans-Golgi network (TGN), a step required for the biosynthesis of cuproenzymes. When Cu + is in excess, ATP7B sequesters Cu + within vesicles that traffic to the canalicular (apical) membrane (Braiterman et al, 2009;Forbes and Cox, 2000;Nyasae et al, 2014), where ATP7B facilitates the extrusion of excess Cu + into the bile (Fanni et al, 2005). Although a few proteins that affect trafficking of ATP7B have been identified, the molecular mechanisms responsible for polarized apical delivery of ATP7B remain poorly understood (Lim et al, 2006a,b;Materia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%